Ізотермічні перерізи систем R2S3–Cu2S–In2S3 (R=La, Pr, Y, Er) при 870 K - Гуч, Михайло Романович; Гулай, Любомир Дмитрович; Олексеюк, Іван Дмитрович; Huch, M. R.; Hulai, Liubomyr D.; Olekseiuk, Ivan D. (Волинський державний університет імені Лесі Українки, 2007)
Взаємодія між компонентами в системах R2S3–Cu2S–In2S3 (R=La, Pr, Y, Er) при 870 К досліджена методами рентгенівської порошкової дифрактометрії. В системі La2S3–In2S3 встановлена кристалічна структура нової тернарної сполуки La3In1,67S7 (структурний тип Сe3Al1,67S7, просторова група P63). У системах R2S3–Cu2S–In2S3 (R=La і Pr) підтверджено існування тетрарних сполук R2CuInS5 (структурний тип La2CuInS5, просторова група Pnma). У системах R2S3–Cu2S–In2S3 (R=Y, Er) виявлено існування тетрарних сполук Y4Cu2In4S13 (структура невідома). Interactions of the components in the R2S3–Cu2S–In2S3 (R=La, Pr, Y, Er) systems at 870 К were investigated using X-ray powder diffraction. The crystal structure of new ternary La3In1,67S7 compound (Сe3Al1,67S7 structure type, space group P63) in the La2S3–In2S3 system was investigated. The formation of the R2CuInS5 (La2CuInS5 structure type, space group Pnma) in the R2S3–Cu2S–In2S3 (R=La and Pr) wa sconfirmed. The formation of new quaternary ~Y4Cu2In4S13 (unknown structure) compounds in the R2S3–Cu2S–In2S3 (R=Y and Er) was estanlished.
Isothermal Sections of the R2S3–Cu2S–In2S3 (R=La, Pr, Y, Er)Systems at 870 K.
Keywords: халькогеніди; сполуки РЗМ; сполуки Cu; сполуки In; сполуки S; ізотермічний перетин; кристалічна структура; сhalcogenides; rare earth compounds; Cu compounds; In compounds; S compounds; isothermalsection; crystal structure